On-line and on-demand Sarawak historical crosswords - Tan, Li Min (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Game based system is a system that performs in an entertainment. form with. fascinating interface to attract users ' attention and the knowledge is gained while they are using this . system. In this project, an on-line and on-demand Sarawak Historical crossword system will be developed. fior who have interested in the history of Sarawak or crossword. This thesis presents the . features. such as topic selection and level of difficulty selection will enhance the performance of crossword system while the users are playing the crossword based on their requirements. The software process model that is chosen to be implemented in this thesis is the waterfall model which provides better management and production. The proposed crossword system interface is designed in an attractive way and easy to understand for obtaining the users' demands. After receiving the users' demands, pairs of clues and definitions that are corresponded with those demands are sent to the EclipseCrossword; a crossword generator that will generate and display the crossword puzzle back to the users. The feedback from testers after using this proposed project is evaluated and majority of the testers agree that the system had met their requirements. The proposed system may encounter the difficulties in the demands must be selected from the topic and followed by the level of difficulty. If the users only want to choose level of difficulty, error may be occurred.